Eriodictyol Suppresses Porphyromonas gingivalis-Induced Reactive Oxygen Species Production by Gingival Keratinocytes and the Inflammatory Response of Macrophages - Maquera-Huacho, Patricia Milagros [UNESP]; Spolidorio, Denise Palomari [UNESP]; Manthey, John. A. A.; Grenier, Daniel (Frontiers Media Sa, 2022)
Porphyromonas gingivalis is a key pathogen of periodontitis, an inflammatory disease that affects the tooth-supporting tissues. The aim of the present study was to investigate the effects of the flavanone eriodictyol on P. gingivalis-induced reactive oxygen species (ROS) production by gingival keratinocytes and the inflammatory response of macrophages. Porphyromonas gingivalis and H2O2 acted synergistically to induce ROS production by keratinocytes. The presence of eriodictyol significantly attenuated ROS production in a dose-dependent manner. We used a macrophage model to show that eriodictyol decreases the secretion of IL-1 beta, IL-6, IL-8, and TNF-alpha induced by P. gingivalis. Evidence has been brought that this anti-inflammatory property of eriodictyol may be related to its ability to prevent the activation of the NF-kappa B signaling pathway by P. gingivalis. This periodontal pathogen was also found to be a potent inducer of matrix metalloproteinase (MMP) production by macrophages, including MMP-2, MMP-8, and MMP-9. Eriodictyol dose-dependently inhibited the production of all three MMPs. Lastly, eriodictyol inhibited the catalytic activity of both MMP-9 and P. gingivalis collagenase. In conclusion, eriodictyol may be a potential therapeutic agent for preventing and/or treating periodontal disease due to its antioxidant, anti-inflammatory, and anti-proteinase properties.
Keywords: eriodictyol; macrophage; keratinocyte; Porphyromonas gingivalis; periodontal disease